Survei Perilaku Pencegahan Covid-19 Pada Masyarakat di Kabupaten Banyumas - Novita Endang Fitriyani; Ikrimah Nafilata; Muhammad Syukri (Jurnal Kesehatan Masyarakat Indonesia, 2021)
Background: Covid 19 is nowadays becoming a global problem. This disease caused by the infection of SARS-Cov-2 and can spread out from human to human by saliva splash. The prevention behavior of this disease are by washing hands with soap on running water for twenty seconds, applying hands with hand sanitizer, wearing mask, preventing crowd, and keeping distance for 1-2 meters. Those efforts, however, are still rarely done by the people. Aims: This research aims to know the covid-19 prevention behavior of people in Banyumas. Method: This research is an observational descriptive research which uses cross-sectional approach. The samples of this research are 450 people, and the data were collected by online questionnaire. Results: the behavior of washing hands using soap on running water for 20 seconds (50.4%), applying hand sanitizer (50.4%), wearing mask in shop, mall, restaurant and other public facilities such as worship places (76.4%), doing activity among the crowd and keeping distance for 1-2 meters (60.2%). Conclusion: There is a need for health education related to Covid-19 prevention to improve behaviour to prevent the transmission of Covid-19, since the respondent proportion in doing prevention is about 90% from entire samples.